A RARE CLINICAL CASE OF HETEROTOPIC PREGNANCY - Фетищева, Лариса Егоровна; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна; Лаврова, Елизавета Владимировна; Ахмадеева, Алена Рамиловна; Мозес, Кира Борисовна; Рудаева, Елена Германовна (Mother and Baby in Kuzbass, 2024)
The article describes a clinical case of heterotopic pregnancy with detection of the ovum in the uterine cavity after salpingectomy for tubal pregnancy. Heterotopic pregnancy is a rare pathology in obstetrics and gynecology. The danger of this disease lies in the violation of the reproductive function of a woman, possible bleeding and death. Among the variants of heterotopic pregnancy, the most common is a combination of uterine and tubal localization. The article discusses the difficulties of diagnosing this condition. Transvaginal ultrasound is the most informative and allows visualizing the ovum in the early stages of pregnancy. Treatment approaches for this type of pathology are also discussed.